Dupilumab for treatment of primary cutaneous amyloidosis in adults: two case reports and literature review - Feiying Guo; Feiying Guo; Feiying Guo; Huajie Zhong; Huajie Zhong; Yuan Wu; Yuan Wu; Xue Xu; Xue Xu; Jiarong Tan; Qiang Zhou; Shunli Tang; et al. (Frontiers in Medicine)
Lichenoid amyloidosis (LA), a subtype of primary cutaneous amyloidosis (PCA), is featured by intensely pruritic, hyperkeratotic papules which lacks standardized treatment. Dupilumab, a human monoclonal antibody targeting for interleukin (IL)-4/13 receptor α chain, is widely applied in type 2 inflammation diseases treatment. This article reported two cases of refractory LA successfully treated with dupilumab and reviewed publications reporting dupilumab treatment for PCA.